Prevalence of Alcohol Use Disorder among Medical Students in New Delhi: A Cross-Sectional Study - Aninda Debnath; Anita Verma; Priyansha Gupta; Sneha Jindal (Indian Journal of Community Medicine)
Background: Amid the global concern over alcohol consumption’s ramifications for public health, the escalating prevalence of alcohol misuse among young individuals, especially students, is alarming. This study examines the prevalence of alcohol use disorder (AUD) among medical students, exploring its link to depression, anxiety, and socioeconomic factors. Material and Methods: We conducted this cross-sectional study at a medical college in New Delhi in the month of June, 2023. We determined a sample size of 425 using prevalence estimates for AUD, a 4% margin of error, and a 15% nonresponse rate. We selected participants using simple random sampling from the MBBS enrollment list and provided them with self-administered questionnaires. We utilized validated screening tools, including PHQ-9, GAD-7, AUDIT-C, and CAGE, to assess depression, anxiety, and AUD. Statistical analysis was performed using STATA 18. AUD prevalence was presented with 95% confidence intervals. Associations between AUD and variables were examined using Chi-square tests. Significant variables (P < 0.2) in univariate analysis were considered in multivariate logistic regression (P < 0.05). Results: In our study, 413 students participated. The prevalence of AUD was 13.6%, depression was 31.5%, and anxiety was 24.2%. Univariate and multivariate logistic regression revealed significant associations between AUD and factors such as gender, current living space, tobacco use, and anxiety. Conclusion: The current study highlights worrisome levels of AUD, depression, and anxiety among medical students in New Delhi. Our research also reveals connections between AUD and factors like gender, living situation, tobacco use, and anxiety.